1997
DOI: 10.1523/jneurosci.17-16-06424.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Septum in the Excitatory Effect of Corticotropin-Releasing Hormone on the Acoustic Startle Reflex

Abstract: Intracerebroventricular administration of corticotropin-releasing hormone (CRH) elicits a constellation of behavioral, autonomic, and endocrinological changes typically observed in stress. One of the behavioral changes after intracerebroventricular CRH is a profound increase of startle amplitude (CRH-enhanced startle). The present study examined the role of the septum in CRHenhanced startle. The septum has direct and indirect connections to the amygdala and inhibits the amygdala. Electrophysiological data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 42 publications
(45 reference statements)
2
17
1
Order By: Relevance
“…In a recent study, we showed that knife cuts of the fimbria/ fornix blocked CRH-enhanced startle, whereas lesions of the dorsal hippocampus did not (Lee and Davis, 1997). Given the fact that the fimbria /fornix is the major output pathway for the hippocampal formation, the failure to block CRH-enhanced startle by either dorsal hippocampal (Lee and Davis, 1997) or ventral hippocampal lesions (current study) is puzzling.…”
Section: Effects Of Chemical Lesions Of the Hippocampus Bnst And Ammentioning
confidence: 57%
See 4 more Smart Citations
“…In a recent study, we showed that knife cuts of the fimbria/ fornix blocked CRH-enhanced startle, whereas lesions of the dorsal hippocampus did not (Lee and Davis, 1997). Given the fact that the fimbria /fornix is the major output pathway for the hippocampal formation, the failure to block CRH-enhanced startle by either dorsal hippocampal (Lee and Davis, 1997) or ventral hippocampal lesions (current study) is puzzling.…”
Section: Effects Of Chemical Lesions Of the Hippocampus Bnst And Ammentioning
confidence: 57%
“…Given the fact that the fimbria /fornix is the major output pathway for the hippocampal formation, the failure to block CRH-enhanced startle by either dorsal hippocampal (Lee and Davis, 1997) or ventral hippocampal lesions (current study) is puzzling. Interestingly, although NMDA lesions of the ventral hippocampus overall failed to block CRH-enhanced startle, f urther investigation of the data revealed that there was a clear dichotomy in lesion effects among ventral hippocampal-lesioned animals.…”
Section: Effects Of Chemical Lesions Of the Hippocampus Bnst And Ammentioning
confidence: 82%
See 3 more Smart Citations